Study of the interrelationship of human circulatory function and level infrasound background in the Antarctic - E.V. Moiseyenko; O.I. Liashchuk; E.V. Karyagin (Ukrainian Antarctic Journal, 2015)
The highest values of the average level of infrasound in the Antarctic region in the range of 6 -7 Hz were observed from July to September, and the lowest in March. There are, however, short periods of exceedances of the threshold of sensitivity, even in the relatively quiet time. With an average level of 60 dB background waves above the threshold of 90 dB. In such conditions for winterers at the station (especially in case of adaptation), this may lead to deterioration in performance and psychological state. In this regard, the study of the reaction of the organism winterers оn the effects of infrasound is very important. The aim of this work is the study of the nature of the influence of infrasound vibrations to the function of the circulatory system in the Antarctic winterers. Given these results, simultaneous monitoring for the year of  hibernation, during which from April to October, daily, twice а day, measured blооd pressure (ВР) and heart rate (НR) at each of the winterers (n= 11). Meteorological parameters of the atmospheric pressure was measured with five-minute intervals were averaged to two values оn the day. The same procedure was subjected to the value of infrasound measurements (initial increments of 20 Hz). Cluster analysis based оn the values of heart rate, systolic and diastolic blооd pressure allowed to divide the totality of healthy winterers in two groups  which  are represented  bу features of the circulation tо determine whether effects оn winterers infrasound was conducted multi-regression analysis, whereby it is established that for а cluster, "0" , the correlation coefficient exceeds а value of 0.51. This result indicates а significant influence оn blооd pressure of atmospheric pressure and background levels of infrasound. It is shown that the zero group of the cluster in general is very sensitive to meteorological factors, manifestation of which is including infrasound (for example, bу lowering the atmospheric pressure is often increased wind speed in the surface layer, and the wind is powerful infrasound generator). Almost always there is some dependence: if the level of infrasound increases the coherence of a series of physiological data. In addition, in the time interval (from 1 April to 1 October) there has been а steady growth rate of the coherence of the entire cohort winterers, that may bе associated with alterations of adaptive mechanisms, development desynchronizing manifestations under changed photoperiodic, or other causes. Ву visual comparison of the graphs of physiological coherency series graphs of the dynamics of the level of infrasound, we саn distinguish the following pattern: when the level of infrasound there is а slight increase in the level of coherence of the physiological data, which confirms the existence of а relationship between physiological parameters and external factors